2017
DOI: 10.14238/pi57.2.2017.84-90
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure-to-height ratio for diagnosing hypertension in adolescents

Abstract: Background Diagnosing hypertension in children and adoles-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In addition, males were taller than females (137.5±14.9 vs. 136.8±15.6 cm; P=0.5). In our study, the SBPHR and DBPHR were significantly correlated with the SBP and DBP which is supported by the results of Ambarita et al 25 They found significant correlations between SBPHR/DBPHR and SBP/DBP (P<0.05); SBPHR and SBP, as well as DBPHR and DBP, had strong, positive correlations. The same results were reported by Guo et al 26 who found that there was a significant positive correlation between the SBPHR and SBP percentiles (r=0.716 for five to 12 years old and r=0.882 for 13 to 18 years old; P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, males were taller than females (137.5±14.9 vs. 136.8±15.6 cm; P=0.5). In our study, the SBPHR and DBPHR were significantly correlated with the SBP and DBP which is supported by the results of Ambarita et al 25 They found significant correlations between SBPHR/DBPHR and SBP/DBP (P<0.05); SBPHR and SBP, as well as DBPHR and DBP, had strong, positive correlations. The same results were reported by Guo et al 26 who found that there was a significant positive correlation between the SBPHR and SBP percentiles (r=0.716 for five to 12 years old and r=0.882 for 13 to 18 years old; P<0.001).…”
Section: Discussionsupporting
confidence: 92%